Effect of Supplementation of Zinc Methionine in Productive Performance and Eggs Quality Traits Laying Hens - Majeed, Noor Talib; Razouqi, Ali Jawad (Journal of agricultural, environmental and veterinary sciences, 2020)
The study was conducted in the field of poultry at the Department of Animal Production/ College of Agriculture- University of Diyala from the period from 21- 1 to 21- 4- 2019. It aimed to study the effect of adding different levels of zinc methionine to the diet in some productive qualities of laying hens. The researcher used 144 chickens (Lohmann Brown) at the age of 21 weeks for the experiment. Randomly distributed to four treatments and zinc methionine was added at a rate of 0, 30, 60, and 90 mg/ kg of diet for the four treatments (T1, T2, T3, T4), respectively. The results of the statistical analysis of the experimtal data showed a significant increase (P
Keywords: Zinc methionine; Egg production ratio; Quality of the veneer quality